Conceptual issues in autism spectrum disorders. Issue 2 (March 2015) - Gallagher, Shaun; Varga, Somogy
Abstract : Purpose of review: To provide an update on recent studies concerning social cognition in autism spectrum disorders (ASDs), to compare different theoretical approaches used to interpret empirical data, and to highlight a number of conceptual issues. Recent findings: In regard to social cognition in ASDs, there is an emerging emphasis on early-onset and prolonged sensory–motor problems. Such sensory–motor problems may fit with the theories of social cognition that emphasize the importance of embodied interaction rather than deficits in mindreading, or they may reflect more general aspects of developmental disorders. Summary: Different theoretical frameworks offer alternative perspectives on the central characteristics in ASDs and motivate different ways of conceptualizing diagnosis and intervention. Theory-of-mind approaches continue to appeal to false-belief paradigms, and debate continues about the performance of individuals with autism. Likewise, there is continuing debate and renewed skepticism about the role of simulation and deficits in the mirror system in ASDs. Growing evidence concerning sensory–motor problems, specifically disrupted patterns in re-entrant (afferent and proprioceptive) sensory feedback across the autistic spectrum, may not only provide support for more embodied interactive approaches, but also suggests that a single approach is unlikely able to explain all social cognition problems in autism. A pluralist approach understands ASDs as involving a variant range of cascading disrupted processes.